The Transformation of Student Character Through Islamic-Based Scouting Activities - Hasniah; Noorthaibah; Fathul Jannah (Journal of Educational Management Research, 2026)
This study aims to examine how character values are transformed through Scouting activities in the context of experiential Islamic education. A qualitative case study approach was employed to explore the process, forms, and impact of character development. Data were collected through observations, in-depth interviews, and documentation involving school leaders, Scout mentors, teachers, and students. Data analysis followed the stages of reduction, presentation, and interactive conclusion drawing. The findings indicate that Scouting activities effectively foster core character values, including discipline, responsibility, independence, cooperation, leadership, and religiosity. The transformation process occurs in three stages: internalization, habituation, and actualization, facilitated by mentors as role models and a supportive religious environment. Experiential activities allow students to internalize values directly, producing tangible and sustainable behavioral changes. The study concludes that Scouting significantly contributes to the holistic development of students’ character socially and spiritually. These results support the theoretical framework of experiential learning-based character education and provide practical guidance for educational administrators to utilize extracurricular programs as a strategic tool for strengthening character education.